Interaction between α1B‐ and other α1− and α2‐adrenoceptors in producing contractions of mouse spleen. Issue 6 (25th September 2021) - Alsufyani, Hadeel A.; Daly, Craig; Docherty, James R.
Abstract: We have investigated the interaction of α1 ‐ and α2 ‐adrenoceptor subtypes in producing isometric contractions to NA in mouse whole spleen. The α1 ‐adrenoceptor antagonist prazosin (10 −8 M) or the α2 ‐adrenoceptor antagonist yohimbine (10 −6 M) alone produced only small shifts in NA potency in wild type (WT) mice, but the combination produced a large shift in NA potency. In spleen from α1A/D ‐KO mice, the effects of prazosin and the combination of prazosin and yohimbine were similar to their effects in WT mice. Hence, in α1A/D ‐KO mice, in which the only α1 ‐adrenoceptor present is the α1B ‐adrenoceptor, prazosin still antagonized contractions to NA. The α1A ‐adrenoceptor antagonist RS100329 (3 × 10 −9 M) produced significant shifts in the effects of higher concentrations of NA (EC50 and EC75 levels) and the α1D ‐adrenoceptor antagonist BMY7378 (3 × 10 −8 M) produced significant shifts in the effects of lower concentrations of NA (EC25 and EC50 levels). The effects of BMY7378 and RS00329 demonstrate α1D ‐adrenoceptor and α1A ‐adrenoceptor components and suggest that the α1B ‐adrenoceptor interacts with an α1D ‐adrenoceptor, and to a lesser extent an α1A ‐adrenoceptor, at low, and an α1A ‐adrenoceptor at high, NA concentrations. This study demonstrates the complex interaction between α1 ‐ and α2 ‐adrenoceptor subtypes in producing contractions of mouse spleen and may have general implications for α‐adrenoceptor mediated control of smooth muscle.